Method for producing gas diffusion electrode substrate

By adding carbon powder and thermosetting resin to the carbon fiber structure and combining the low-temperature heat treatment process, the high cost and insufficient performance caused by high-temperature heat treatment are solved, and a gas diffusion electrode substrate with high conductivity and chemical stability is achieved, which improves the gas supply and performance of fuel cells.

JP7626065B2Active Publication Date: 2025-02-04TORAY INDUSTRIES INC
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2021516706
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-03-30
Filing Date
2021-03-18
Publication Date
2025-02-04
Estimated Expiration
2041-03-18

AI Technical Summary

Technical Problem

During the manufacturing process of gas diffusion electrode substrates of existing fuel cells, high-temperature heat treatment leads to high costs and insufficient conductivity and chemical stability, and the accumulation of water droplets affects the gas supply.

Method used

The low-temperature heat treatment process is adopted to form a microporous layer by adding carbon powder and thermosetting resin with good conductivity to the carbon fiber structure, avoiding high-temperature heat treatment, and using materials such as carbon nanotubes to improve conductivity and chemical stability.

Benefits of technology

The high conductivity and chemical stability of gas diffusion electrode substrates are achieved at low cost, reducing water droplet accumulation and improving the performance of fuel cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007626065000001
    Figure 0007626065000001
Patent Text Reader

Abstract

The objective of the present invention is to provide a method which is for producing a gas diffusion electrode substrate having a high conductivity and a chemical resistance, and by which an increase in production cost can be suppressed. The present invention is a method for producing a gas diffusion electrode substrate in which a microporous layer is formed in a conductive porous body formed by bonding carbon fibers to each other by means of a cured product of a binder resin, the method having, in the following order: a binder resin impregnation step in which a carbon fiber structure is impregnated with a binder resin composition to obtain a pre-impregnated body; a coating step in which the surface of the pre-impregnated body is coated with a microporous layer coating solution; and a heat treatment step in which the pre-impregnated body that has been subjected to the coating step is heat-treated at a temperature of at least 200 °C, wherein the binder resin composition is a liquid composition including a binder resin and a carbon powder, the binder resin being a thermosetting resin, and the method does not have a step for heat-treating the pre-impregnated body at a temperature of at least 200 °C, between the binder resin impregnation step and the heat treatment step.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing a gas diffusion electrode substrate suitable for use in an electrode of a fuel cell, particularly a polymer electrolyte fuel cell. [Background technology]

[0002] In recent years, with the rise of global environmental concern, there has been growing expectation for energy sources that do not emit carbon dioxide, and in particular, hydrogen-fueled fuel cells have attracted attention. A fuel cell is a type of power generation device that supplies a fuel gas containing hydrogen to the anode and an oxidizing gas containing oxygen to the cathode, generating electromotive force through an electrochemical reaction that occurs at both electrodes.

[0003] Among fuel cells, a polymer electrolyte fuel cell is particularly versatile. A polymer electrolyte fuel cell is generally constructed by stacking a separator, a gas diffusion electrode substrate, a catalyst layer, an electrolyte membrane, a catalyst layer, a gas diffusion electrode substrate, and a separator in this order. Of these, specifically, a conductive porous body such as carbon felt, carbon paper, or carbon cloth made of carbon fiber is used as the gas diffusion electrode substrate.

[0004] Conductive porous bodies are required to have spring properties that can absorb dimensional changes in the thickness direction of the electrolyte membrane, so carbon fibers are often bound with a binder. Resin carbides, which provide high electrical conductivity, are widely used as such binders. However, to obtain resin carbides, a process is required in which the porous body is heat-treated in an inert atmosphere at 1000°C or higher after the resin is applied.

[0005] In addition, because the fibers of the gas diffusion electrode substrates described above are coarse, large water droplets are generated when water vapor condenses, and the water droplets adhere to the electrode surface, easily causing flooding, which is a condition that prevents the supply of gas to the electrode. For this reason, a microporous layer (MPL) made of conductive fine particles such as carbon powder may be provided on the conductive porous body. MPL is generally formed by applying a coating liquid (hereinafter referred to as MPL coating liquid) in which carbon powder, fluororesin particles as a binder, and a surfactant are dispersed in water to the surface of the conductive porous body, followed by drying and sintering.

[0006] Therefore, in order to produce a gas diffusion electrode substrate having MPL, it is usually necessary to carry out a heat treatment for firing the resin charcoal and a heat treatment for sintering the MPL coating liquid to form MPL. However, this requires multiple large-scale heating furnaces, which increases the manufacturing cost.

[0007] Therefore, in Patent Document 1, carbon powder such as carbon black or graphite is mixed into the porous body and the heat treatment temperature is lowered to reduce costs. In Patent Document 2, split fibers having fibril parts are included in the porous body to ensure electrical conductivity and chemical resistance, and an attempt is made to omit the heating step for producing the resin carbide. [Prior art documents] [Patent documents]

[0008] [Patent Document 1] International Publication No. 2001 / 022509 [Patent Document 2] JP 2004-363018 A Summary of the Invention [Problem to be solved by the invention]

[0009] In Patent Document 1, although carbon fibers can be bonded together by a relatively low-temperature heat treatment, the heat treatment temperature of the porous body is preferably 400° C. or higher, and more preferably 450° C. or higher, in order to increase the chemical resistance of the binder, and if the MPL is heat-treated in this temperature range, the water repellent agent contained in the MPL will thermally decompose. Therefore, when the MPL is provided, it is necessary to carry out the heat treatment twice, and the cost reduction is limited.

[0010] On the other hand, in Patent Document 2, the cost can be kept low because no heat treatment is involved, but the electrical conductivity is low, resulting in reduced fuel cell performance.

[0011] An object of the present invention is to provide a method for producing a gas diffusion electrode substrate having high electrical conductivity and chemical resistance while suppressing production costs. [Means for solving the problem]

[0012] In order to solve the above-mentioned problems, the present invention provides a method for producing a gas diffusion electrode base material in which a microporous layer is formed on a conductive porous body in which carbon fibers are bonded together with a cured binder resin, the method comprising the steps of: a binder resin impregnation step of impregnating a carbon fiber structure with a binder resin composition to obtain a pre-impregnated body; a coating step of applying a microporous layer coating liquid to the surface of the pre-impregnated body; and a heat treatment step of heat-treating the pre-impregnated body that has undergone the coating step at a temperature of 200°C or higher, in this order; wherein the binder resin composition is a liquid composition containing a thermosetting resin and carbon powder, and the method for producing a gas diffusion electrode base material does not include a step of heat-treating the pre-impregnated body at a temperature of 200°C or higher between the binder resin impregnation step and the heat treatment step. Effect of the Invention

[0013] By using the method for producing a gas diffusion electrode material of the present invention, it is possible to obtain a gas diffusion electrode material having excellent electrical conductivity and chemical resistance while suppressing production costs. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] [Conductive porous body] In the present invention, the term "gas diffusion electrode substrate" refers to a carbon fiber structure having a certain shape, such as a paper sheet, from carbon fibers (e.g., a carbon fiber paper sheet in a state in which the carbon fibers are only bonded with an organic polymer such as polyvinyl alcohol, as described below), which is then impregnated with a binder resin to form a pre-impregnated body, in which the binder resin is cured to bind the carbon fibers together, and further a microporous layer is formed on the surface.

[0015] The conductive porous body in the present invention (hereinafter, sometimes simply referred to as "porous body") is a porous structure having a sheet-like form formed by bonding carbon fibers together. As such a porous body, a carbon fiber paper sheet, a carbon fiber fabric, a carbon fiber nonwoven fabric, etc. can be used. As long as the carbon fibers are bonded together, the porous body also includes a porous body in which gaps or cracks occur between the binder resin cured product and the carbon fibers.

[0016] As the conductive porous body, a carbon fiber paper sheet is preferred because it has a property of absorbing dimensional changes in the direction perpendicular to the surface of the electrolyte membrane, i.e., has excellent "springiness." Note that the carbon fiber paper sheet here refers to a sheet-like substrate in which carbon fibers are randomly distributed in a two-dimensional plane.

[0017] The carbon fiber paper body can be manufactured by a wet papermaking method in which carbon fibers are dispersed in a liquid, or a dry papermaking method in which carbon fibers are dispersed in air. Among them, the wet papermaking method is preferably used because of its excellent productivity. The carbon fiber paper body may be manufactured by mixing carbon powder or organic fibers to improve the electrical conductivity and drainage of the gas diffusion electrode substrate. In addition, for the purpose of improving shape retention and handling properties, the carbon fiber paper body may be manufactured by using an organic polymer such as polyvinyl alcohol, polyvinyl acetate, polyacrylonitrile, or cellulose as an adhesive.

[0018] Examples of carbon fibers constituting the porous body include polyacrylonitrile (PAN)-based, pitch-based, and rayon-based carbon fibers. Among these, PAN-based carbon fibers and pitch-based carbon fibers are preferably used because of their excellent mechanical strength.

[0019] The carbon fibers constituting the porous body preferably have an average diameter of single fibers (hereinafter referred to as "carbon fiber diameter") in the range of 3 to 20 μm, more preferably in the range of 5 to 10 μm. When the carbon fiber diameter is 3 μm or more, more preferably 5 μm or more, the diameter of the pores becomes large, the drainage property improves, and flooding can be easily suppressed. On the other hand, when the carbon fiber diameter is 20 μm or less, more preferably 10 μm or less, the thickness unevenness is reduced, and it is easy to control the thickness of the porous body to a preferable range described later. Here, the carbon fiber diameter can be determined by taking a photograph of the carbon fiber at 1000 times magnification using a microscope such as a scanning electron microscope, randomly selecting 30 different single fibers, measuring their diameters, and averaging the diameters.

[0020] In addition, the carbon fibers constituting the porous body preferably have an average length of the single fibers (hereinafter referred to as "carbon fiber length") within the range of 3 to 20 mm, more preferably within the range of 5 to 15 mm. When the carbon fiber length is 3 mm or more, more preferably 5 mm or more, the porous body tends to have excellent mechanical strength, electrical conductivity, and thermal conductivity. On the other hand, when the carbon fiber length is 20 mm or less, more preferably 15 mm or less, the dispersion of the carbon fibers is excellent, and a homogeneous porous body is easily obtained. Carbon fibers having such a carbon fiber length can be obtained by a method of cutting continuous carbon fibers to a desired length. The carbon fiber length was measured by taking a photograph of the carbon fibers at 50 times magnification using a microscope such as a scanning electron microscope, randomly selecting 30 different single fibers, and measuring their lengths to obtain an average value.

[0021] [Binder resin impregnation process] The method for producing a gas diffusion electrode substrate of the present invention includes a binder resin impregnation step of impregnating the carbon fibrous structure as described above with a binder resin composition to obtain a pre-impregnated body. In the present invention, the binder resin composition is a liquid composition containing a thermosetting resin and carbon powder.

[0022] The thermosetting resin may be a phenol resin, an epoxy resin, a melamine resin, a furan resin, etc. A mixture of these thermosetting resins with a thermoplastic resin is also preferably used.

[0023] As the carbon powder, graphite such as flake graphite, scaly graphite, amorphous graphite, artificial graphite, expanded graphite, and flake graphite can be used. Carbon black such as furnace black, acetylene black, lamp black, and thermal black, and nanocarbon materials such as carbon nanotubes and carbon nanofibers can be particularly preferably used. Nanocarbon materials easily form conductive paths with a small amount, and can achieve the effect of reducing conductive resistance with a smaller amount added than graphite with a large particle size.

[0024] As the binder resin composition, it is preferable to use a liquid composition in which the binder resin and carbon powder are dispersed in a solvent. When dispersing the binder resin and carbon powder in a solvent, the binder resin and carbon powder are added to the solvent, and then strong shear is applied to improve the dispersibility of the carbon powder, so that the carbon powder can be uniformly attached to the carbon fiber structure. As a method for applying strong shear, for example, a method of stirring with a homogenizer at a rotation speed of 3000 rpm or more for 10 minutes or more can be mentioned.

[0025] Methods for impregnating the carbon fiber structure with the binder resin composition include a method for immersing the carbon fiber structure in a liquid binder resin composition prepared by adding a solvent to carbon powder and a binder resin, a method for applying the binder resin composition to the carbon fiber structure, etc. Among these, the method for immersing the carbon fiber structure in a liquid binder resin composition is particularly preferably used because of its excellent productivity.

[0026] When the carbon fiber structure is impregnated with the binder resin composition, it is preferable to impregnate the carbon fiber in the pre-impregnated body with 10 to 400 parts by mass of the binder resin, and more preferably with 20 to 300 parts by mass. When the binder resin is 10 parts by mass or more, more preferably 20 parts by mass or more, per 100 parts by mass of the carbon fiber in the pre-impregnated body, it is possible to attach a sufficient amount of carbon powder to obtain high conductivity while containing uncarbonized resin in the porous body. On the other hand, when the binder resin is 400 parts by mass or less, more preferably 300 parts by mass or less, per 100 parts by mass of the carbon fiber in the pre-impregnated body, the porous body has excellent gas diffusivity while maintaining its conductivity.

[0027] When graphite is used as the carbon powder, it is preferable to mix the graphite and the binder resin in the binder resin composition so that the graphite is 150 to 400 parts by mass per 100 parts by mass of the binder resin, and it is more preferable to mix the graphite and the binder resin in the binder resin composition so that the graphite is 170 to 350 parts by mass per 100 parts by mass of the binder resin.

[0028] When the pre-impregnated body contains 150 parts by mass or more, more preferably 170 parts by mass or more of graphite per 100 parts by mass of binder resin, a porous body having excellent electrical conductivity and excellent chemical resistance due to the graphite covering the binder resin is obtained. On the other hand, when the graphite is 400 parts by mass or less, more preferably 350 parts by mass or less, the graphite adheres uniformly to the carbon fiber structure during impregnation, and the porous body has excellent gas diffusion properties. Chemical resistance means that the binder performance is less likely to deteriorate due to oxidative deterioration of the resin and the electrical conductivity is less likely to decrease even when power generation is repeated.

[0029] In particular, when a nanocarbon material is used as the carbon powder, excellent conductivity can be obtained with the addition of a small amount compared to the use of ordinary graphite, so it is preferable to mix the nanocarbon material and the binder resin in the binder resin composition so that the nanocarbon material is 30 to 200 parts by mass per 100 parts by mass of binder resin, and it is more preferable to mix the nanocarbon material and the binder resin in the binder resin composition so that the nanocarbon material is 50 to 100 parts by mass.

[0030] When the amount of the nanocarbon material per 100 parts by mass of the binder resin is 30 parts by mass or more, more preferably 50 parts by mass or more, a porous body having both electrical conductivity and chemical resistance can be obtained. On the other hand, when the amount of the nanocarbon material per 100 parts by mass of the binder resin is 200 parts by mass or less, more preferably 100 parts by mass or less, the nanocarbon material adheres uniformly to the carbon fibrous structure during impregnation, and the porous body has excellent gas diffusivity.

[0031] The thickness of the porous body is preferably 50 to 230 μm, more preferably 70 to 180 μm. When the thickness of the porous body is 230 μm or less, more preferably 180 μm or less, the gas diffusion is easily increased and the generated water is easily discharged. Furthermore, the size of the fuel cell as a whole is easily reduced. On the other hand, when the thickness of the porous body is 50 μm or more, more preferably 70 μm or more, gas diffusion in the in-plane direction inside the porous body is efficiently performed, and power generation performance is easily improved. The thickness of the porous body is determined by the following method. The porous body is placed on a smooth surface plate, and the difference in height between the case with and without the measurement object is measured under a pressure of 0.15 MPa. Sampling is performed at 10 different locations, and the average of the measured height differences is taken as the thickness.

[0032] [Water repellent application process] The method for producing a gas diffusion electrode substrate of the present invention may include a water repellent applying step of applying a water repellent containing a fluororesin to the pre-impregnated body before the coating step described below. As the fluororesin contained in the water repellent, one or more resins selected from polytetrafluoroethylene (PTFE), tetrafluoroethylene hexafluoropropylene copolymer (FEP), perfluoroalkoxy fluororesin (PFA), ethylene tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF), and polyvinyl fluoride (PVF) can be used. Among them, PTFE or FEP, which exhibits strong water repellency, is preferable. When applying a water repellent containing a fluororesin to the pre-impregnated body, the amount of the fluororesin contained in the pre-impregnated body is not particularly limited, but is appropriately about 1% by mass or more and 10% by mass or less with respect to the mass of the entire pre-impregnated body. By making it 1% by mass or more, sufficient water repellency is exhibited, and by making it 10% by mass or less, it is possible to easily secure pores that serve as gas diffusion paths or drainage paths while exhibiting water repellency.

[0033] When the water repellent is applied as described above, the water repellent treatment is carried out using a water repellent treatment liquid in which the water repellent containing a fluororesin is dispersed. Examples of the water repellent treatment method include a method of immersing the pre-impregnated body in the water repellent treatment liquid and a method of applying the water repellent treatment liquid to the pre-impregnated body by die coating or the like. From the viewpoint of uniformly distributing the fluororesin in the porous body in the direction perpendicular to the surface, the method of immersing the pre-impregnated body in the water repellent treatment liquid is preferred. After the water repellent treatment, a heating and drying process may be carried out, but in the present invention, even in this case, heat treatment at a temperature of 200°C or higher is not carried out as described below.

[0034] [Coating process] The method for producing a gas diffusion electrode substrate of the present invention next includes a coating step of coating the surface of the obtained pre-impregnated body with an MPL coating liquid. As described above, the MPL coating liquid is a coating liquid in which carbon powder, a water repellent, and, if necessary, a dispersion aid such as a surfactant are dispersed in water.

[0035] Examples of carbon powder contained in the MPL coating liquid include graphite such as flake graphite, flaky graphite, amorphous graphite, artificial graphite, expanded graphite, and flake graphite; carbon black such as furnace black, acetylene black, lamp black, and thermal black; carbon nanotubes; and carbon nanofibers. Of these, carbon black is preferably used.

[0036] As the water repellent contained in the MPL coating liquid, fluororesins such as polytetrafluoroethylene (PTFE), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), and tetrafluoroethylene-perfluoroalkylvinyl ether copolymer (PFA) are preferably used.

[0037] As the dispersing agent, it is preferable to use a nonionic surfactant.

[0038] The MPL coating liquid can be applied to the surface of the pre-impregnated body by a coating method such as screen printing, rotary screen printing, spray atomization, intaglio printing, gravure printing, die coater coating, bar coating, or blade coating.

[0039] [Heat treatment process] The manufacturing method of the present invention further includes a heat treatment step in which the pre-impregnated body in a state in which the MPL coating liquid has been applied through the coating step is heat-treated at a temperature of 200°C or higher. By heating at a temperature of 200°C or higher, the water repellent agent contained in the MPL coating liquid melts, and the MPL coating liquid is sintered and converted into MPL. The heating temperature in the heat treatment step is preferably 200 to 400°C, more preferably 300 to 400°C.

[0040] After the heat treatment step, the MPL becomes a porous layer having an average pore size of usually 0.01 μm to 1 μm. The basis weight of the MPL is not particularly limited, but is preferably 5 to 50 g / m after the heat treatment. 2 It is preferable that the range is 10 to 30 g / m 2 More preferably, the weight of the MPL is 5 g / m 2 More preferably, 10 g / m2 When the weight of the MPL is 50 g / m or more, one surface of the porous body can be covered with the MPL, the back diffusion of the generated water is further promoted, and the drying of the electrolyte membrane can be further suppressed. 2 Less than or equal to 30 g / m 2 When the thickness is equal to or less than this, the drainage property is further improved and flooding can be further suppressed.

[0041] [Drying process] If necessary, a drying step may be performed before the heat treatment step, in which the pre-impregnated body that has been subjected to the coating step is dried at a temperature of 80 to 180° C. in order to volatilize the water in the MPL coating liquid.

[0042] However, in the manufacturing method of the present invention, there is no step of substantially heat-treating the pre-impregnated body at a temperature of 200°C or higher between the binder resin impregnation step and the heat treatment step. In a typical manufacturing method of a gas diffusion electrode base material, a step of performing heat treatment at 1000°C or higher in an inert atmosphere before applying the MPL coating liquid to carbonize the binder resin is provided in order to impart electrical conductivity and chemical resistance to the binder resin. In the manufacturing method of the present invention, since the heat treatment step before applying the MPL coating liquid is omitted, the binder resin that does not have electrical conductivity remains in the porous body. However, by including a certain amount of highly conductive carbon powder as the binder resin composition, electrical conductivity and chemical resistance can be ensured even with a single heat treatment after applying the MPL coating liquid. EXAMPLES

[0043] <Evaluation of Conductive Resistance> The electrical resistance in the direction perpendicular to the surface of the gas diffusion electrode substrate was calculated by cutting the gas diffusion electrode substrate to 30 mm x 30 mm, sandwiching it between two gold-plated plates, applying a uniform surface pressure of 1.0 MPa, passing a current of 1.0 A through it, measuring the resistance at that time, and multiplying it by the area of ​​the substrate.

[0044] <Evaluation of power generation performance of polymer electrolyte fuel cells> A catalyst solution was prepared by adding, in order, 1.00 g of platinum-supported carbon (manufactured by Tanaka Kikinzoku Kogyo Co., Ltd., platinum loading: 50% by mass), 1.00 g of purified water, 8.00 g of Nafion (registered trademark) solution (5.0% by mass of Nafion (registered trademark) manufactured by Aldrich), and 18.00 g of isopropyl alcohol (manufactured by Nacalai Tesque, Inc.).

[0045] Next, the catalyst solution was sprayed onto "Naflon (registered trademark)" PTFE tape "TOMBO (registered trademark)" No. 9001 (manufactured by Nichias Corporation) cut to 5 cm x 5 cm, and then dried at room temperature to obtain a platinum content of 0.3 mg / cm. 2 A PTFE sheet with a catalyst layer was produced. Next, a solid polymer electrolyte membrane "Nafion (registered trademark)" NRE-211CS (manufactured by DuPont) cut to 8 cm x 8 cm was sandwiched between two PTFE sheets with a catalyst layer, and pressed at a temperature of 130°C for 5 minutes while applying a pressure of 5 MPa with a flat plate press, thereby transferring the catalyst layer to the solid polymer electrolyte membrane. After pressing, the PTFE sheet was peeled off to produce a solid polymer electrolyte membrane with a catalyst layer.

[0046] Next, the solid polymer electrolyte membrane with the catalyst layer was sandwiched between two gas diffusion electrode substrates cut to 5 cm x 5 cm, and pressed at 130°C for 5 minutes while applying a pressure of 3 MPa using a flat press to produce a membrane electrode assembly. The gas diffusion electrode substrate was positioned so that the surface with the microporous layer was in contact with the catalyst layer side.

[0047] The obtained membrane electrode assembly was assembled into a single cell for fuel cell evaluation, and the voltage was measured when the current density was changed. A serpentine separator with a single flow channel, with a groove width, groove depth, and rib width of 1.0 mm, was used as the separator. In addition, unpressurized hydrogen was supplied to the anode side, and unpressurized air was supplied to the cathode side, and the evaluation was performed.

[0048] Both hydrogen and air were humidified using a humidifier pot set at 70°C. The humidity was 100%. The oxygen utilization rates in the hydrogen and air were 70mol% and 40mol%, respectively, and the cell temperature was 70°C. The current density was 1.5A / cm 2 The output voltage was measured and used as an index of power generation performance.

[0049] Example 1 Polyacrylonitrile carbon fiber manufactured by Toray Industries, Inc. was cut to a length of 12 mm, dispersed in water, made into paper, and further immersed in a 10% by mass aqueous dispersion of polyvinyl alcohol and dried to obtain a carbon fiber basis weight of approximately 20 g / m 2 A long carbon fiber paper sheet (carbon fiber structure) was obtained and wound into a roll.

[0050] A dispersion (binder resin composition) was prepared by mixing phenolic resin, flake graphite (average particle size 5 μm), and methanol in a mass ratio of phenolic resin, flake graphite, and methanol of 2:7:91. The carbon fiber structure cut to 10 cm×10 cm was immersed in the dispersion, and after being pulled out, the structure was squeezed with a mangle to remove excess liquid. The carbon fiber structure was then dried at a temperature of 100° C. for 10 minutes, and after drying, 50 parts by mass of phenolic resin were attached to 100 parts by mass of carbon fiber, and 350 parts by mass of flake graphite were attached to 100 parts by mass of phenolic resin, to obtain a pre-impregnated body.

[0051] Next, the pre-impregnated body was subjected to a heat and pressure treatment at 180°C for 5 minutes while being pressed by a flat press. During pressing, a spacer was placed on the flat press to adjust the distance between the upper and lower press plates so that the thickness after heat treatment would be 130 μm. The pre-impregnated body was then immersed in an aqueous dispersion of PTFE resin ("Polyflon (registered trademark)" PTFE dispersion D-210C (manufactured by Daikin Industries, Ltd.)) to impregnate the pre-impregnated body with a fluororesin. After immersion in the PTFE aqueous dispersion, the pre-impregnated body was pulled out and dried, and 5 parts by mass of PTFE was attached to 100 parts by mass of the pre-impregnated body.

[0052] Finally, an MPL coating solution containing carbon black, PTFE, and "TRITON (registered trademark)" X-100 (manufactured by Nacalai Tesque, Inc.) as a surfactant in a mass ratio of 3:1:6 was applied to one side of the pre-impregnated body after the water-repellent treatment, and the coating was heat-treated at 380°C for 10 minutes to form a microporous layer of approximately 20 g / m. 2 A gas diffusion electrode substrate having the above structure was obtained.

[0053] Example 2 A gas diffusion electrode substrate was obtained in the same manner as in Example 1, except that the carbon fiber structure was immersed in a binder resin composition in which phenolic resin, flake graphite, and methanol were mixed in a mass ratio of 2:3:95, and impregnated with 50 parts by mass of phenolic resin per 100 parts by mass of carbon fiber and 154 parts by mass of flake graphite per 100 parts by mass of phenolic resin.

[0054] Example 3 A gas diffusion electrode substrate was obtained in the same manner as in Example 1, except that acetylene black "Denka Black (registered trademark)" (manufactured by Denka Co., Ltd.) was used instead of flake graphite, and the carbon fiber structure was immersed in a binder resin composition in which phenolic resin, acetylene black, and methanol were mixed in a mass ratio of 2:2:96, and the carbon fiber structure was impregnated with 50 parts by mass of phenolic resin per 100 parts by mass of carbon fiber and 83 parts by mass of acetylene black per 100 parts by mass of phenolic resin.

[0055] Example 4 A gas diffusion electrode substrate was obtained in the same manner as in Example 1, except that furnace black "Ketjen Black (registered trademark)" (manufactured by Lion Specialty Chemicals Co., Ltd.) was used instead of flake graphite, and the carbon fiber structure was immersed in a binder resin composition in which phenol resin, furnace black, and methanol were mixed in a mass ratio of 2:2:96, and the carbon fiber structure was impregnated with 50 parts by mass of phenol resin per 100 parts by mass of carbon fiber and 83 parts by mass of furnace black per 100 parts by mass of phenol resin.

[0056] Example 5 A gas diffusion electrode substrate was obtained in the same manner as in Example 1, except that linear carbon vapor-grown carbon fiber (carbon nanotube) "VGCF (registered trademark)" (manufactured by Showa Denko K.K.) was used instead of flake graphite, and the carbon fiber structure was immersed in a binder resin composition in which phenolic resin, carbon nanotubes, and methanol were mixed in a mass ratio of 2:2:96, and impregnation was performed so that 50 parts by mass of phenolic resin was used per 100 parts by mass of carbon fiber and 83 parts by mass of carbon nanotubes were used per 100 parts by mass of phenolic resin.

[0057] Example 6 A gas diffusion electrode substrate was obtained in the same manner as in Example 1, except that acetylene black "Denka Black (registered trademark)" (manufactured by Denka Co., Ltd.) was used instead of flake graphite, and the carbon fiber structure was immersed in a binder resin composition in which phenolic resin, acetylene black, and methanol were mixed in a mass ratio of 3:1:96, and the carbon fiber structure was impregnated with 50 parts by mass of phenolic resin per 100 parts by mass of carbon fiber and 36 parts by mass of acetylene black per 100 parts by mass of phenolic resin. Comparative Example 1 A gas diffusion electrode substrate was obtained in the same manner as in Example 1, except that the carbon fiber structure was immersed in a binder resin composition in which phenol resin and methanol were mixed in a mass ratio of 7:93, and impregnated with 50 parts by mass of phenol resin per 100 parts by mass of carbon fiber.

[0058] Table 1 shows the evaluation results of the electrical resistance and power generation performance (output voltage) of the gas diffusion electrode substrates produced in the respective Examples and Comparative Examples.

[0059] [Table 1]

Claims

1. A method for producing a gas diffusion electrode substrate comprising: forming a microporous layer on a conductive porous body in which carbon fibers are bound together by a cured product of a binder resin; a binder resin impregnation step of impregnating the carbon fiber structure with a binder resin composition to obtain a pre-impregnated body; a coating step of coating a microporous layer coating liquid on the surface of the pre-impregnated body; a heat treatment step of heat treating the pre-impregnated body having undergone the coating step at a temperature of 200° C. or higher; in that order, the binder resin composition is a liquid composition containing a binder resin and carbon powder, The binder resin is a thermosetting resin, A method for producing a gas diffusion electrode substrate, which does not include a step of heat treating the pre-impregnated body at a temperature of 200° C. or higher between the binder resin impregnation step and the heat treatment step.

2. 2. The method for producing a gas diffusion electrode substrate according to claim 1, wherein in the binder resin impregnation step, the carbon fiber structure is impregnated with the binder resin composition so that the binder resin is 10 to 400 parts by mass per 100 parts by mass of the carbon fibers in the pre-impregnated body.

3. The method for producing a gas diffusion electrode substrate according to claim 1 or 2, wherein the carbon fibrous structures are carbon fiber paper sheets.

4. The method for producing a gas diffusion electrode substrate according to any one of claims 1 to 3, wherein the carbon powder is graphite.

5. 5. The method for producing a gas diffusion electrode substrate according to claim 4, wherein the binder resin composition contains 150 to 400 parts by mass of graphite per 100 parts by mass of the binder resin.

6. The method for producing a gas diffusion electrode substrate according to any one of claims 1 to 3, wherein the carbon powder is a nanocarbon material selected from carbon black, carbon nanotubes, and carbon nanofibers.

7. 7. The method for producing a gas diffusion electrode substrate according to claim 6, wherein the binder resin composition contains 30 to 200 parts by mass of the nano carbon material per 100 parts by mass of the binder resin.

8. The method for producing a gas diffusion electrode substrate according to any one of claims 1 to 7, further comprising a water repellent applying step of applying a water repellent containing a fluororesin to the pre-impregnated body prior to the coating step.

9. The method for producing a gas diffusion electrode substrate according to any one of claims 1 to 8, further comprising a drying step of drying the pre-impregnated body subjected to the coating step at a temperature of 80 to 180°C prior to the heat treatment step.

10. The method for producing a gas diffusion electrode substrate according to any one of claims 1 to 9, wherein the heat treatment temperature in the heat treatment step is 200 to 400°C.

Citation Information

Patent Citations

  • Porous carbon board and its manufacturing method

    JP2004311431A

  • Porous electrode base material for polymer electrolyte fuel cell

    JP2004363018A

  • Gas diffusion layer for fuel cell and manufacturing method of the same

    JP2018152270A

  • Porous, electrically conductive sheet and method for production thereof

    WO2001022509A1